Über die Grenzwertsätze für grosse Abweichungen - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Алешкявичене. О предельных теоремах для больших уклоненийA. Aleškevičienė. Apie ribines teoremas dideliems atsilenkimams